DAMPAK RUMPUT ALAM DAN RUMPUT UNGGUL DALAM RANSUM SERTA PENGARUHNYA TERHADAP ERFORMA TERNAK (Influence of forage sources on ration quality and dairy cattle performances) - Afsitin Joan Tatra; Luki Abdullah; Despal Despal (Buletin Ilmu Makanan Ternak, 2015)
Forage offers to lactating cows by KPSBU Lembang cooperatives member mainly cultivated grass or natural grass with/without agricultural byproduct (non-cultivated). The different sources of forage offered influence the ration quality and nutrient intake of dairy cattle which may affect their performances (milk production and quality, body weight, Body condition (BCS) and manure score). A study to evaluate the influence of different forage sources on lactating cows’ performances have been conducted. Eight lactating cows were used to study 2 types of forage sources (cultivated forage and non-cultivated forage) as treatments with each treatment was repeated four times. The amount of feed offers have been weight, their nutrient contents and utilities (proximate composition, structural carbohydrate, mineral Ca and P, fermentability and digestibility) have been determined in laboratory, their metabolizable and net energy for lactation have been estimated. The animal performances have been measured and observed. The results showed that the source of forage significantly influence the nutrients offers. Farmers who used cultivated forage offered higher nutrients (crude lipid, crude protein, nitrogen free extract and digested crude protein) to their cows which resulted in higher milk production (14.8 vs. 11.9 l h-1 d-1) and BCS (2.6 vs. 2.3). Keywords : cultivated, dairy cattle, forage, intake, nutrient